Cepheid Xpert® Flu/RSV and Seegene Allplex™ RP1 show high diagnostic agreement for the detection of influenza A/B and respiratory syncytial viruses in clinical practice. Issue 2 (20th August 2020) - Wabe, Nasir; Lindeman, Robert; Post, Jeffrey J.; Rawlinson, William; Miao, Melissa; Westbrook, Johanna I.; Georgiou, Andrew
Abstract: Background: Molecular assays based on reverse transcription‐polymerase chain reaction (RT‐PCR) provide reliable results for the detection of respiratory pathogens, although diagnostic agreement varies. This study determined the agreement between the RT‐PCR assays (Xpert ® Flu/RSV vs Allplex ™ RP1) in detecting influenza A, influenza B, and respiratory syncytial viruses (RSVs) in clinical practice. Methods: We retrospectively identified 914 patient encounters where testing with both Xpert ® Flu/RSV and Allplex ™ RP1 was undertaken between October 2015 and September 2019 in seven hospitals across New South Wales, Australia. The diagnostic agreement of the two assays was evaluated using positive percent agreement, negative percent agreement, and prevalence and bias‐adjusted kappa. Results: The positive percent agreement was 95.1% for influenza A, 87.5% for influenza B, and 77.8% for RSV. The negative percent agreement was 99.4% for influenza A, 99.9% for influenza B, and 100% for RSV. The prevalence and bias‐adjusted kappa was 0.98 for influenza A, 0.99 for influenza B, and 0.97 for RSV. In a sensitivity analysis, the positive percent agreement values were significantly higher during the non‐influenza season than the influenza season for influenza B and RSV. Conclusions: The Xpert ® Flu/RSV and Allplex ™ RP1 demonstrated a high diagnostic agreement for all three viruses assessed. The seasonal variation in the positive percent agreement of the two assays for influenza B and RSV may have been due to lower numbers assessed, variability in the virology of infections outside the peak season, or changes in the physiology of the infected host in different seasons.